Makerere University Students’ Learning Challenges Associated with COVID-19 Pandemic Lockdown: A Case of Department of Adult and Community Education - Mugula , Oscar; Momanyi, Marcella (African Journal of Education,Science and Technology (AJEST), 2021)
This study aimed to examine the challenges that were faced by university students because of COVID-19 lockdown and suggested interventions. The objectives of the study were to; identify the challenges associated with COVID-19 that were faced by students, and suggest interventions for continuity of learning by students at Makerere University. A descriptive survey design was followed and convenience sampling of students from the Department of Adult and Community Education was employed. Data was collected using a questionnaire, adapted and modified from ITHAKA S+R. The study revealed that the most significant challenges that students faced during lockdown included; balancing school, work, and home responsibilities, using digitalized documents, and accessing Makerere University E-learning Environment system (MUELE). From the findings, even those who can use these resources, they can try up to 60%. Interventions have been recommended in this study.